Answer:
![h = 12](https://tex.z-dn.net/?f=h%20%3D%2012)
![x = 9](https://tex.z-dn.net/?f=x%20%3D%209)
![y= 16](https://tex.z-dn.net/?f=y%3D%2016)
Step-by-step explanation:
Given
The attached triangle
Required
Find h, x and y
Let the base of the triangle be 15.
So, the area is:
![A = \frac{1}{2} * 15 * 20](https://tex.z-dn.net/?f=A%20%3D%20%5Cfrac%7B1%7D%7B2%7D%20%2A%2015%20%2A%2020)
![i.e\ height = 20](https://tex.z-dn.net/?f=i.e%5C%20height%20%3D%2020)
![A = \frac{1}{2} * 300](https://tex.z-dn.net/?f=A%20%3D%20%5Cfrac%7B1%7D%7B2%7D%20%2A%20300)
![A = 150](https://tex.z-dn.net/?f=A%20%3D%20150)
Let the base of the triangle be 25.
So, the area is:
![A = \frac{1}{2} * 25 * h](https://tex.z-dn.net/?f=A%20%3D%20%5Cfrac%7B1%7D%7B2%7D%20%20%2A%2025%20%2A%20h)
![i.e\ height = h](https://tex.z-dn.net/?f=i.e%5C%20height%20%3D%20h)
![A = \frac{1}{2} * 25h](https://tex.z-dn.net/?f=A%20%3D%20%5Cfrac%7B1%7D%7B2%7D%20%20%2A%2025h)
Substitute ![A = 150](https://tex.z-dn.net/?f=A%20%3D%20150)
![\frac{1}{2}*25h = 150](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%2A25h%20%3D%20150)
Solve for h
![h = \frac{150 *2}{25}](https://tex.z-dn.net/?f=h%20%3D%20%5Cfrac%7B150%20%2A2%7D%7B25%7D)
![h = 6 *2](https://tex.z-dn.net/?f=h%20%3D%206%20%2A2)
![h = 12](https://tex.z-dn.net/?f=h%20%3D%2012)
Considering the smallest triangle
![Hypotenuse = 15](https://tex.z-dn.net/?f=Hypotenuse%20%3D%2015)
So:
![15^2 = h^2 + x^2](https://tex.z-dn.net/?f=15%5E2%20%3D%20h%5E2%20%2B%20x%5E2)
![15^2 = 12^2 + x^2](https://tex.z-dn.net/?f=15%5E2%20%3D%2012%5E2%20%2B%20x%5E2)
This gives:
![15^2 - 12^2 = x^2](https://tex.z-dn.net/?f=15%5E2%20-%2012%5E2%20%3D%20x%5E2)
![81 = x^2](https://tex.z-dn.net/?f=81%20%3D%20x%5E2)
Take square roots
![9 =x](https://tex.z-dn.net/?f=9%20%3Dx)
![x = 9](https://tex.z-dn.net/?f=x%20%3D%209)
Solving for y
![x + y = 25](https://tex.z-dn.net/?f=x%20%2B%20y%20%3D%2025)
![y= 25 - x](https://tex.z-dn.net/?f=y%3D%2025%20-%20x)
![y= 25 - 9](https://tex.z-dn.net/?f=y%3D%2025%20-%209)
![y= 16](https://tex.z-dn.net/?f=y%3D%2016)
I would say 504 basing it off of converting 2/3 into 4/6 and used sets of 84 to each be 1/6
Answer:
seven divided by the difference of ten and three
seven over the difference of ten and three
-33 / 11 = ?
-33/11
Simplify
-3/1 would be the answer
Answer:
Set
−
3
+
3
√
3
i
equal to
0
.
−
3
+
3
√
3
i
=
0
Since
−
3
+
3
√
3
i
≠
0
, there are no solutions.
Step-by-step explanation: